2011
DOI: 10.5194/bgd-8-4163-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Labile Fe(II) concentrations in the Atlantic sector of the Southern Ocean along a transect from the subtropical domain to the Weddell Sea Gyre

Abstract: Labile Fe(II) distributions were investigated in the Sub-Tropical South Atlantic and the Southern Ocean during the BONUS-GoodHope cruise from 34 to 57° S (February–March 2008). Concentrations ranged from below the detection limit (0.009 nM) to values as high as 0.125 nM. In the surface mixed layer, labile Fe(II) concentrations were always higher than the detection limit, with values higher than 0.060 nM south of 47° S, representing between 39% and 63% of dissolved Fe (DFe). Biological production was evidenced.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 111 publications
(133 reference statements)
0
12
0
Order By: Relevance
“…The atmospheric Fe(II) concentrations in aerosols increased from a lower value of 0.13 ng m −3 at ~ 40°S to 0.33 ng m −3 at ~ 58°S, the same latitudinal region studied by Sarthou et al . [], and the spatial distribution of atmospheric Fe(II) deposition showed a similar trend with increasing values toward high latitudes. Though the Fe(II) properties in seawater and in the marine atmosphere are driven by different processes, this similar trend may reveal certain levels of coupled processes affecting Fe(II) in the air‐sea interface in the Southern Ocean.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The atmospheric Fe(II) concentrations in aerosols increased from a lower value of 0.13 ng m −3 at ~ 40°S to 0.33 ng m −3 at ~ 58°S, the same latitudinal region studied by Sarthou et al . [], and the spatial distribution of atmospheric Fe(II) deposition showed a similar trend with increasing values toward high latitudes. Though the Fe(II) properties in seawater and in the marine atmosphere are driven by different processes, this similar trend may reveal certain levels of coupled processes affecting Fe(II) in the air‐sea interface in the Southern Ocean.…”
Section: Resultsmentioning
confidence: 73%
“…Recent measurements in the Atlantic sector of the Southern Ocean by Sarthou et al . [] showed that higher values of labile Fe(II) were found in the surface mixed layer than the values in the deep waters, and relatively high values of labile Fe(II) (0.060 nM) were found south of 47°S, accounting for 39–63% of the total dissolved Fe in the surface mixed layer. The atmospheric Fe(II) concentrations in aerosols increased from a lower value of 0.13 ng m −3 at ~ 40°S to 0.33 ng m −3 at ~ 58°S, the same latitudinal region studied by Sarthou et al .…”
Section: Resultsmentioning
confidence: 99%
“…At low O 2 concentrations the oxidation rate of Fe(II) to Fe(III) is reduced such that high (nM) concentrations of Fe(II) can be found in the water column26. For example, in the Southern Ocean Sarthou et al 27. measured Fe(II) half-lives with respect to oxidation of 3–11 min in surface seawater (at pH 8.0–8.1 and O 2 234–353 μM), whereas Scholz et al 28.…”
Section: Resultsmentioning
confidence: 99%
“…Most or all of the iron should be in the ferric state (oxidation state III), because ferrous iron (oxidation state II) rapidly becomes oxidized to ferric iron in water of pH > 6, for any oxygen pressure above a small minimum value, conditions that are well satisfied in seawater (Cornell & Schwertmann, , p. 340). In the surface waters of the Southern Ocean, where oxygen is abundant, 40–60% of the dissolved iron can be Fe (II) (Sarthou et al, ), but in those surface waters it is apparently produced by biological reduction, which is unlikely to be active beneath an ice shelf, where sunlight is absent.…”
Section: Light Absorption By Iron‐oxide Mineralsmentioning
confidence: 99%